If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57 = -7(7b + -3) + -1(7 + -6b) Reorder the terms: 57 = -7(-3 + 7b) + -1(7 + -6b) 57 = (-3 * -7 + 7b * -7) + -1(7 + -6b) 57 = (21 + -49b) + -1(7 + -6b) 57 = 21 + -49b + (7 * -1 + -6b * -1) 57 = 21 + -49b + (-7 + 6b) Reorder the terms: 57 = 21 + -7 + -49b + 6b Combine like terms: 21 + -7 = 14 57 = 14 + -49b + 6b Combine like terms: -49b + 6b = -43b 57 = 14 + -43b Solving 57 = 14 + -43b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '43b' to each side of the equation. 57 + 43b = 14 + -43b + 43b Combine like terms: -43b + 43b = 0 57 + 43b = 14 + 0 57 + 43b = 14 Add '-57' to each side of the equation. 57 + -57 + 43b = 14 + -57 Combine like terms: 57 + -57 = 0 0 + 43b = 14 + -57 43b = 14 + -57 Combine like terms: 14 + -57 = -43 43b = -43 Divide each side by '43'. b = -1 Simplifying b = -1
| 6x+6=3x | | 26-5x=-7-3r | | 4(u-4)-6u=4 | | 20-4(2w+1)=6w-4(6+w) | | (-8y-5)(7y)y=-3 | | 8c-3d=6 | | 1d+8=2d-17 | | 0.7m+0.3m=2m-4 | | p=m+k+n | | -6(x-3)-4(6-6x)=12 | | -6-3(6+4x)=-24-2x | | 91=-7(2n-7) | | -5*(1/9+x)=0 | | 114=(x+2)15-3x | | -(4y+3z-4)= | | x+1(2)+x(2)=14 | | 2x+8=8+2x | | 18=c+5/2 | | (x+2)(x-1)(x+1)=0 | | -5a+2a=12-15 | | 15-2(2w+1)=7w-2(7+w) | | -187=2-7(4x+7) | | 9l=3m | | 5(-5-3p)=-8p+3 | | 7t-(t-4)=25 | | (4a-4)(4a-1)=0 | | 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) |